Legitimacy without legitimation of the lopsided parliament. The snap parliamentary elections in Macedonia 2014 - Mikucka-Wójtowicz, Dominika (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2015)
This paper is devoted to the snap parliamentary elections in Macedonia, which took place on 27 April 2014. The main initiator of the early elections was the DUI, which represents the interests of the Albanian minority and was the junior coali¬tion partner in the government led by Nikola Gruevski from the VMRO-DPMNE. The DUI’s activists did not want to advocate the candidacy of the incumbent head of state, Gjorge Ivanov, who was seeking re-election. After the elections the SDSM, the main rival of the ruling VMRO-DPMNE, has not recognised the result and refused to take up their parliamentary seats.

Niniejszy artykuł jest poświęcony analizie przedterminowych wyborów parlaparlamentarnych w Macedonii, które odbyły się 27 kwietnia 2014 roku. Ich głównym inicjatorem była reprezentująca interesy mniejszości albańskiej DUI, która dotychczas pełniła rolę koalicjanta rządzącej VMRO-DPMNE premiera Nikoli Gruevskiego. Kością niezgody, która doprowadziła do przedterminowej elekcji, była odmowa poparcia przez działaczy DUI kandydatury wspieranego przez konserwatystów i ubiegającego się o reelekcję szefa państwa - Borde Ivanova. Mimo to po wyborach doszło do odnowienia dotychczas rządzącej koalicji. Natomiast główny rywal VMRO-DPMNE-SDSM nie uznała ich wyników i konsekwentnie od kilku miesięcy odmawia objęcia zdobytych mandatów.
Prawomocność bez legitymizacji asymetrycznego parlamentu. Przyspieszone wybory parlamentarne w Macedonii w 2014 r.
Keywords: Macedonia; parliamentary elections; early elections; Macedonia; wybory parlamentarne; przedterminowe wybory